2013
DOI: 10.1177/0333102412475238
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of benign and inflammatory manifestations of Tolosa-Hunt syndrome

Abstract: Benign and inflammatory THS were highly similar in terms of nosography. The responses to glucocorticoid treatment were generally good except in patients with orbital pseudotumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…There is not sufficient evidence for the appropriate dose, route of administration and duration of therapy 12. A remarkable feature of glucocorticoid therapy is the rapid resolution of the orbital pain within 1–3 days, which also serves as diagnostic confirmation 10 13. Our patient responded in a similar manner.…”
Section: Discussionsupporting
confidence: 74%
“…There is not sufficient evidence for the appropriate dose, route of administration and duration of therapy 12. A remarkable feature of glucocorticoid therapy is the rapid resolution of the orbital pain within 1–3 days, which also serves as diagnostic confirmation 10 13. Our patient responded in a similar manner.…”
Section: Discussionsupporting
confidence: 74%
“…However, other conditions such as lymphoma, sarcoidosis, and meningioma can have similar findings and the clinician must keep these in mind when interpreting MRI results [2,5,39,40]. Infrequently, the MRI can be normal in patients with THS [9,12,33,38,[41][42][43]. In this study, MRI demonstrated cavernous sinus enhancement in all patients whose initial MRI was normal.…”
mentioning
confidence: 53%
“…An initial prednisolone dose of 1.0 to 1.5 mg/kg/day is commonly found in available reports. However, the therapeutic effect reportedly does not differ between doses above and below 0.5 mg/kg/day [14]. The patient in this case was an elderly man of small stature; consequently, there were concerns over adverse reactions to corticosteroid therapy, and dose modulation was required.…”
Section: Discussionmentioning
confidence: 79%